Modeling by Using Linear First-Order Difference Equations and its Application in Economics - rahim, Brahim; Baghdoud, Radhia (Finance and Business Economies Review, 2022)
This research discusses the modeling by using linear difference equations that conclude to understand and explain different economic phenomena, we have divided this research into two parts, the first one focused in the Linear First-Order Difference Equations with Constant Coefficients with example like explaining the “Cobweb” model to study the relationship between supply & demand and Harrod model to study the relationship between national income and economic growth. As for the second one was about case study: entitled modeling the impact of government support on the budget balance in Algeria. We have founded that using modeling by using linear first-order difference equations with constant coefficients offers opportunities for the researchers in economics to model Economic phenomena in equations, and by trying to solve those equations to reach logic results, to eventually analyzingand explaining those results based on mathematical model.